The Need for Mobile Cancer Services in Rural Communities - Inastyarikusuma, Tarrinni; Kusumawaty, Ira; Yunike, Yunike; Sri Ananingsih, Esti; Podojoyo, Podojoyo; Elfrida, Sotha; Monalisa, Monalisa (Yayasan Rumah Ilmu Professor, 2024)
Cancer is one of the leading causes of death globally, including in Indonesia. However, access to cancer health services in rural areas is still minimal. This study explores mobile cancer services' needs and potential benefits in rural Indonesian communities. This research method is qualitative, with data collection through in-depth interviews and surveys of residents in various villages in several provinces. The research results show that rural communities face significant challenges in accessing cancer services, such as long distances to health facilities, limited transportation, a shortage of medical personnel trained in oncology, and a lack of information about early detection and treatment of cancer. Most respondents stated that the cost and time required to travel to big cities prevented them from getting timely diagnosis and treatment. Mobile cancer services, consisting of mobile medical units with diagnostic equipment and trained medical personnel, can overcome these barriers. Research finds that mobile services have great potential to improve early cancer detection through routine screening at strategic locations in rural areas. In addition, this service can provide health education regarding cancer prevention and healthy lifestyles, increasing public awareness of the importance of routine check-ups. The participation of the local community, including community leaders and health cadres, is critical to the success of this service. Collaboration between governments, non-governmental organizations, and the private sector is needed to provide and fund mobile cancer services. An inclusive and sustainable financing model is required. This study concludes that mobile cancer services are urgently needed in rural Indonesian communities. Implementation of these services can reduce disparities in access to cancer care and save many lives through early detection and timely intervention. Health policies that support mobile cancer services need to be implemented immediately, taking into account the specific conditions of each region